A inaplicabilidade da lei de execução penal e seus reflexos nos reclusos e egressos do cárcere em Sorocaba - Almeida, Gustavo Portela Barata de (2008)
The present research has been originated with the objective of verifying the applicability or not of the rules contained in the Law of Penal Execution and the reflexes of this inapplicability or partial applicability in the life of the cloistered and the prison egress. The work was based on field researches done at Sorocaba s Criminal Execution s Trial Court and with the local prison directors and the cloistered and egresses of these prisons. In the first chapter we have outlined the evolution of the penalty and its finality. In the second chapter we have analyzed the main rules contained at the LEP (Law of Penal Execution) regarding the assistance of the rights assured to the imprisoned, as well as analyzed the attributions destined to the execution organs. On chapter three we presented the actual research and in the last chapter we have outlined a parallel between what is established by law and the reality experienced in prison quotidian. Different means of confrontation and prove are brought to quote where we can conclude to be a reduction of the finality and reach the norms asserted in the Law of Penal Execution, despite its non applicability by means of the governmental organs in a way to become a dead letter inside the current legal injunction